Evaluation of dose distribution in thoracic vertebral metastases in the different schedules of radiotherapy used in clinical practice - Wesołowska, Iwona; Wydmański, Jerzy; Miszczyk, Leszek; Majewski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2003)
Objective: The objective of this study is an evaluation of the dose prescription depth and beam energy on dose distribution in thoracic vertebral metastases and normal tissues. Material and methods: In 20 patients there were performed CT-based dose distributions for hypothetical vertebral metastases to Th1, Th6 and Th12. Using the selected beam energies (g, 6 MV photons and 20 MV photons) and different dose prescription depths (build-up and 5 cm) six treatment plans were performed for each case. Dose distributions in vertebral metastases and normal tissues were evaluated. The ±20% range of the prescribed dose in PTV was considered as acceptable. Results: The minimal dose in metastases ranged from 3.2 Gy using gamma beams to 5.6 Gy using 20 MV photons. The application of 20 MV photons gave 85% of acceptable treatment plans for build-up and 92% for the depth of 5 cm. The normalization at the 5 cm depth allowed to achieve 51% of acceptable plans for 6 MV photons and 22% for gamma beams. The normalization in build-up resulted in unacceptable distribution for both. The maximum dose in normal tissue was 8.4 Gy for 20 MV photons, 9.5 Gy for 6 MV photons and 10.5 Gy for gamma beams. Conclusions: On the basis of obtained results we can conclude that acceptable plans were obtained only for 20 MV photons and they indicate the necessity of individual treatment planning for patients with bone metastases.